PENENTUAN NASABAH PENERIMA REWARD PRODUK GOLD DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) STUDI KASUS : PT. PINJAM INDONESIA: Riki Ruli A. Siregar, Faizal Fachrurrozi - Jurnal, Redaksi Tim (PETIR, 2019)
As an appreciation to their customer, PT Pinjam Indonesia has a Gold product. Gold is a product that allows customer to get 10% discount of total bill every 6 months, and is given to two customers. Until now, PT Pinjam Indonesia has difficulties in deciding which customer from Online mortgage system deserves to be rewarded with the Gold product, this problem occurs because of the many numbers of customer in the system. Therefore, Decision Support System is needed to help speed up and make the deciding process easier. Decision Support System decide the highest alternative value that deserves to receive the Gold product using the Simple Additive Weighting (SAW) method wtih prescribedcriterias. The basic concept of Simple Additive Weighting (SAW) method is to find the weighted additive from performance rating of every alternative’s attributes. SAW method needs a normalization process of the decision matrix to a scale that can be compared with every rated alternatives. A calculation process is applied to all the criterias to get the result of which alternative is best to receive the Gold product. This method could help the decision making process to be more objective.